Mineralogia e liberação de potássio em solos de várzea do Rio Grande do Sul - Britzke, Darines (2010)
The cultivation of flooded rice in Rio Grande do Sul (RS) does not always respond to potassium (K) fertilization, even when the availability is considered low or medium. Other K forms not estimated by the method of analysis (Mehlich-1) are contributing to the supply to plants. The aim of this work was to study the mineralogy and the potential release K in paddy soils from RS. The experiment was carried out in laboratory, using samples from 15 lowland soils of 13 municipalities of RS, produce with flooded rice. The K extraction was done using the following methods: ammonium acetate, sodium tetraphenyl borate (NaTFB) and hydrofluoric acid (HF). In some samples, selected by the content of total K, the minerals present in these soils were identified by X-ray diffraction (XRD) analysis. To assess the potential release of nonexchangeable K NaTFB was used with times of reaction from 1 up to 96 hours (contact soil / extraction solution). On this way, the XRD was used to verify the possible changes in the mineralogy after NaTFB contact with the soil. There was a wide variation in K among the soils and in the levels of nonexchangeable K extracted in different times of reaction, that probably reflect on the K availability to plants. Soils with low or medium levels of K total showed similar caly minerals and the soils with high K total level contained illite reflects. Besides, only the Santa Maria and Caçapava do Sul soils, which had high nonexchengeable K, the mineralogy of the illite present in the clay fraction was affected by NaTFB extractor with 24 hours of contact.